The digital person : technology and privacy in the information age - Solove, Daniel J. (New York University Press, 2004)
Seven days a week, twenty-four hours a day, electronic databases are compiling information about you. As you surf the Internet, an unprecedented amount of your personal information is being recorded and preserved forever in the digital minds of computers. For each individual, these databases create a profile of activities, interests, and preferences used to investigate backgrounds, check credit, market products, and make a wide variety of decisions affecting our lives. The creation and use of these databases—which Daniel J. Solove calls “digital dossiers”—has thus far gone largely unchecked. In this startling account of new technologies for gathering and using personal data, Solove explains why digital dossiers pose a grave threat to our privacy. The Digital Person sets forth a new understanding of what privacy is, one that is appropriate for the new challenges of the Information Age. Solove recommends how the law can be reformed to simultaneously protect our privacy and allow us to enjoy the benefits of our increasingly digital world. The first volume in the series EX MACHINA: LAW, TECHNOLOGY, AND SOCIETY